2017
DOI: 10.1177/2325967117728922
|View full text |Cite
|
Sign up to set email alerts
|

Early Sport Specialization: Effectiveness and Risk of Injury in Professional Baseball Players

Abstract: Background:The rate of early sport specialization in professional baseball players is unknown.Purpose:To report the incidence and age of sport specialization in current professional baseball players and the impact of early specialization on the frequency of serious injuries sustained during the players’ careers. We also queried participants about when serious injuries occurred, the players’ current position on the field, and their opinions regarding the need for young athletes to specialize early to play at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 17 publications
4
44
0
3
Order By: Relevance
“…Professional baseball players who participated only in baseball (single-sport athletes) before high school were more likely to suffer major injuries during their professional careers than players who participated in additional sports (multiple-sport athletes). 44 These studies seem to indicate the prophylactic benefits of performing multiple sports in childhood and adolescence rather than focusing on a single sport.…”
Section: Injury Riskmentioning
confidence: 97%
See 2 more Smart Citations
“…Professional baseball players who participated only in baseball (single-sport athletes) before high school were more likely to suffer major injuries during their professional careers than players who participated in additional sports (multiple-sport athletes). 44 These studies seem to indicate the prophylactic benefits of performing multiple sports in childhood and adolescence rather than focusing on a single sport.…”
Section: Injury Riskmentioning
confidence: 97%
“…Several groups 43,44 have looked at injury risk in young specialized athletes. Rugg et al 43 identified current NBA players who were drafted in the first round from 2008 to 2015 and investigated whether they participated in additional sports (multiple-sport athletes) or played only basketball (single-sport athletes) during high school.…”
Section: Injury Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…While much previous research has focused on coaches' knowledge (Fiander, Jones, & Parker, 2013;Lewis, Morgan, & Cooper, 2015;Andronikos et al, 2015), research should also consider the knowledge and strategies implemented by parents (Elliott, Drummond, & Knight, 2017;Harwood & Knight, 2016;Knight, Dorsch, Osai, Haderlie, & Sellars, 2016). Misunderstandings of youth development are likely to lead to problems in relation to early specialisation such as dropout (Crane & Temple, 2015;Fraser-Thomas, Côté, & Deakin, 2008) and injury (Hall, Foss, Hewett, & Myer, 2015;Wilhelm, Choi, & Deitch, 2017).…”
mentioning
confidence: 99%
“…Individuals completed the 3-point sport specialization questionnaire 12 that asked whether they had met 3 ice hockey participation criteria at any point before grade 9 of high school. 18 The questions for each criterion were as follows:…”
Section: Methodsmentioning
confidence: 99%